Characterization of the deoxyhemoglobin binding site on human erythrocyte band 3: implications for O(2) regulation of erythrocyte properties - Chu, Haiyan (American Society of Hematology, 2008)
Band 3, the major protein of the human erythrocyte membrane, associates with multiple metabolic, ion transport, and structural proteins. Functional studies demonstrate that the oxygenation state of the erythrocyte regulates cellular properties performed by these and/or related proteins. Because deoxyhemoglobin, but not oxyhemoglobin, binds band 3 reversibly with high affinity, these observations raise the hypothesis that hemoglobin might regulate erythrocyte properties through its reversible, oxygenation-dependent association with band 3. To explore this hypothesis, we have characterized the binding site of deoxyHb on human erythrocyte band 3. We report that (1) deoxyHb binds to residues 12-23 of band 3; (2) mutation of residues on either side of this sequence greatly enhances affinity of deoxyHb for band 3, suggesting that evolution of a higher affinity interaction would have been possible had it been beneficial for survival; (3) Hb does not bind to 2 other sequences in band 3 despite their high sequence homology to residues 12-23, and (4) the Hb binding site on band 3 lies proximal to binding sites for glycolytic enzymes, band 4.1 and ankyrin, suggesting possible mechanisms through which multifarious erythrocyte properties might be regulated by the oxygenation state of the cell.